Organizational Readiness and Barriers to Digital Transformation in Indonesian SMEs - Lutfiani, Ninda; Wijono, Sutarto; Dwi Purnomo, Hindriyanto; Zakaria, Noor Azura (APTISI Transactions on Management (ATM), 2025)
Digital transformation (DT) is essential for enhancing competitiveness, ef- ficiency, and innovation in the digital era. However, Small and Medium En- terprises (SMEs) in Indonesia face significant barriers to adopting digital tech- nologies due to limited resources, lack of digital skills, and environmental con- straints. This study aims to assess the organizational readiness and identifybarriers to DT adoption among Indonesian SMEs using the Technology Organization Environment (TOE) framework. A survey of 210 SMEs from various sectors was conducted to evaluate their readiness levels and perceived barriers. The results indicate that while SMEs show moderate technological readiness, organizational readiness remains low, primarily due to inadequate human re- source competencies, resistance to change, and limited financial capacity. Addi- tionally, environmental factors such as regulatory uncertainty and weak institu- tional support further impede progress. This study contributes to the existing literature by highlighting the specific challenges faced by SMEs in emerging economies, particularly Indonesia. Based on the findings, the study offers prac- tical recommendations for policymakers, industry associations, and SME own- ers to enhance organizational readiness and mitigate barriers, accelerating the digital transformation process for SMEs in Indonesia.